Topological Polymer Chemistry Enters Surface Science: Linear versus Cyclic Polymer Brushes. Issue 50 (24th October 2016) - Morgese, Giulia; Trachsel, Lucca; Romio, Matteo; Divandari, Mohammad; Ramakrishna, Shivaprakash N.; Benetti, Edmondo M.
Abstract: The cyclic polymer topology strongly alters the interfacial, physico‐chemical properties of polymer brushes, when compared to the linear counterparts. In this study, we especially concentrated on poly‐2‐ethyl‐2‐oxazoline (PEOXA) cyclic and linear grafts assembled on titanium oxide surfaces by the "grafting‐to" technique. The smaller hydrodynamic radius of ring PEOXAs favors the formation of denser brushes with respect to linear analogs. Denser and more compact cyclic brushes generate a steric barrier that surpasses the typical entropic shield by a linear brush. This phenomenon, translates into an improved resistance towards biological contamination from different protein mixtures. Moreover, the enhancement of steric stabilization coupled to the intrinsic absence of chain ends by cyclic brushes, produce surfaces displaying a super‐lubricating character when they are sheared against each other. All these topological effects pave the way for the application of cyclic brushes for surface functionalization, enabling the modulation of physico‐chemical properties that could be just marginally tuned by applying linear grafts. Abstract : Cyclic polymer brushes : The cyclic polymer topology strongly alters the interfacial properties of polymer brushes. The smaller hydrodynamic volume coupled with the distinctive cyclic architecture generates surface assemblies with increased grafting density, augmented steric stabilization, improved antifouling and lubrication properties with respect to linear brush counterparts.